(untitled) (LEGAL DIALOGICA, 2025)
This research aims to find out and analyze the rights of heirs with mental disorders from a civil law perspective. As well as knowing and analyzing the legal consequences of the division of inheritance rights with mental disorders according to the Civil Code. This research is a type of normative legal research that is legal research that is carried out by researching literature materials or legal materials by taking issues from law as a norm system used, normative legal research makes the norm system the center of study. The results of this study show that (1). The inheritance rights of mental disorders are still fully recognized as legal subjects who are entitled to receive a share of the inheritance. However, due to the inability to act legally, the individual must be placed under guardianship according to the provisions of Article 433 of the Civil Code. (2). As a result of the law on the distribution of inheritance rights with mental disorders according to the Civil Code, they are still entitled to receive inheritance as long as they meet the inheritance requirements (Article 832 of the Civil Code). However, because it is considered incompetent by law, the implementation and management of inheritance rights is carried out by a court-appointed guardian (Article 433 of the Civil Code). The supervisor is obliged to submit periodic reports to the court (Article 448 of the Civil Code), and can be revoked and replaced if he abuses his authority (Article 452 of the Civil Code). Thus, the support system functions as a legal protection mechanism for the inheritance rights of ODGJ. Abstrak: Penelitian ini bertujuan mengetahui dan menganalisis hak ahli waris dengan gangguan mental dalam perspektif hukum perdata. Serta mengetahui dan menganalisis akibat hukum pembagian hak waris dengan gangguan mental menurut KUH Perdata. Penelitian ini ialah jenis penelitian hukum normatif merupakan penelitian hukum yang dilakukan dengan cara meneliti bahan pustaka atau Bahan Hukum dengan mengambil isu dari hukum sebagai sistem norma yang digunakan maka penelitian hukum normatif menjadikan sistem norma sebagai pusat kajian. Hasil penelitian ini menunjukkan bahwa (1).Hak waris gangguan mental tetap diakui secara penuh sebagai subjek hukum yang berhak menerima bagian warisan. Namun, karena ketidakmampuan untuk bertindak secara hukum, individu tersebut harus ditempatkan di bawah pengampuan sesuai ketentuan Pasal 433 KUH Perdata. Akibat hukum pembagian hak waris dengan gangguan mental menurut KUH Perdata, tetap berhak menerima warisan selama memenuhi syarat kewarisan (Pasal 832 KUH Perdata). Namun, karena dianggap tidak cakap hukum, pelaksanaan dan pengelolaan hak warisnya dilakukan oleh pengampu yang ditunjuk pengadilan (Pasal 433 KUH Perdata). Pengampu wajib menyampaikan laporan berkala kepada pengadilan (Pasal 448 KUH Perdata), dan dapat dicabut serta diganti jika menyalahgunakan wewenangnya (Pasal 452 KUH Perdata). Dengan demikian, sistem pengampuan berfungsi sebagai mekanisme perlindungan hukum terhadap hak waris ODGJ.